FIND THE ANSWERS

F(x)=x^2-12 x and g(x)=x + 6 (f)(g)= ?

Answer this question

Do you know the correct answer? Make money answering questions! Join now.
  • F(x)=x^2-12 x and g(x)=x + 6 (f)(g)= ?


Answers

Operations on Functions. First you learned ... = 3x – 5x + 2 + 4 = –2x + 6 (f – g)(x) = f(x) – g(x) = [3x + 2] – [4 – 5x] = 3x + 5x + 2 – 4 ...
Read more
Positive: 76 %
Composition of Functions: ... ". And "( f o g)(x)" means "f (g(x))". ...
Read more
Positive: 73 %

More resources

Simplifying (f + g)(x) = 6x 2 + -12y + -19 + x 3 + -1x 2 + -8x + -1 Reorder the terms for easier multiplication: x ... !0! | | 6(x-8)+32=2(x-6) | | 0=1/x-2 ...
Read more
Positive: 76 %
We have already seen some functions that are the inverse of each other. The functions f(x) = x 2 and g(x) = √x are the inverse of each other if we ...
Read more
Positive: 71 %
Note that f ( x ) = 3 and g ( x ) = 2, so, h ( x ) = ... = 6 x + 9 + 6 x-2 = 12 x + 7 . Introductory Calculus (University of Calgary) Fall 2014 6 / 10 ...
Read more
Positive: 57 %
G0(x) = f(x) for allx 2(a;b). Then Z b a f(x)dx = G(b) G(a) Example Evaluate the definite integral Z 1 0 ... = 6x5. 5 To find definite integral, have to ...
Read more
Positive: 34 %

Show more results